2019
DOI: 10.1016/j.molmet.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal plasticity of insulin and incretin secretion and insulin sensitivity following sleeve gastrectomy contribute to sustained improvements in glucose control

Abstract: ObjectiveBariatric surgery acutely improves glucose control, an effect that is generally sustained for years in most patients. The acute postoperative glycemic reduction is at least partially mediated by enhanced incretin secretion and islet function, and occurs independent of caloric restriction, whereas the sustained improvement in glucose control is associated with increased insulin sensitivity. However, studies in humans with bariatric surgery suggest that these elevations are not static but undergo coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
4
2
Order By: Relevance
“…Our results also differed from those of Mokadem et al. in the post-operative time course (6–7 weeks versus 28 days in our study) which is characterized by a progressive increase of glycemia over time and possible reduction of meal-stimulated incretin and insulin secretion following the RYGBP in ob/ob mice [71] . Hao et al., [69] reported that, in ob/ob mice, body weight was reduced by RYGB transiently in the first week, recovered in the second week and increased over the baseline thereafter.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results also differed from those of Mokadem et al. in the post-operative time course (6–7 weeks versus 28 days in our study) which is characterized by a progressive increase of glycemia over time and possible reduction of meal-stimulated incretin and insulin secretion following the RYGBP in ob/ob mice [71] . Hao et al., [69] reported that, in ob/ob mice, body weight was reduced by RYGB transiently in the first week, recovered in the second week and increased over the baseline thereafter.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences with our results may be explained, first, by differences in surgical technique since Mokadem et al performed a Roux-en-Y reconstruction of the gastrointestinal tract with two anastomosis (distal transected jejunal limb to the proximal anterior gastric wall and the proximal transected jejunal limb to the afferent Roux limb). Our results also differed from those of Mokadem et al in the post-operative time course (6À7 weeks versus 28 days in our study) which is characterized by a progressive increase of glycemia over time and possible reduction of meal-stimulated incretin and insulin secretion following the RYGBP in ob/ob mice [71]. Hao et al, [69] reported that, in ob/ob mice, body weight was reduced by RYGB transiently in the first week, recovered in the second week and increased over the baseline thereafter.…”
Section: Discussioncontrasting
confidence: 99%
“…We further assessed the ability of 7 to block endogenous incretin action on glucose control in the context of an oral glucose tolerance test. We injected mice with either vehicle or 7 (500 nmol/kg and 1500 nmol/kg) 1 h prior to an oral gavage of glucose at a dose demonstrated to stimulate endogenous GIP secretion ( Figure 5 C,D) [ 30 , 31 ]. Pretreatment with the high dose of peptide 7 worsened glucose control in this context, indicating that peptide 7 can antagonize endogenous incretin action in mice in the dose range tested here.…”
Section: Resultsmentioning
confidence: 99%
“…In most VSG and RYGB studies, GLP-1 and PYY levels are found to be elevated after the surgeries. In studies done in rats and mice, GLP-1 level was elevated after VSG and RYGB ( 18 , 19 ). Numerous studies done in humans show similar findings.…”
Section: Gut Hormonesmentioning
confidence: 99%